Socio-psychological risks of different generations in the digitalisation of society - V. N. Voronin; M. V. Iontseva; L. Yu. Shuraeva (Вестник университета)
Due to the development of digital technologies and the accelerated digitalisation of society, problems of a socio-psychological nature are emerging. The essence, characteristic features and reaction of each generation to modern trends are considered. The risk factors of global digitalisation for all generations of modern society are identified. The ways of minimising the consequences of socio-psychological risks for each generation of modern society are proposed. The main trends of accelerated digitalisation of society and their impact on the socio-psychological aspects of personality, the structure of cognitive processes and its cognitive components are considered. The essence of each of the five generations is analysed, starting from the older generation of Baby boomers and ending with the new generation of Alpha, their distinctive features, risk factors and value orientations. The authors propose possible ways to minimise the consequences of socio-psychological risks for each generation. The purpose and objective of the study: using the example of the considered five generations to show the socio-psychological risks to which modern society is exposed and to determine ways to minimise them. Research methods: comparative and socio-cultural analysis. Research tools – the theory of generations. As a result of the conducted research, socio-psychological problems were identified and options for their minimisation with the help of scientific knowledge achievements were proposed. Organisational, economic and socio-psychological mechanisms make it possible to reduce risks with the intensive development of the digitalisation of society and maintain a harmonious relationship between different generations.